FRI0559 ASSOCIATION BETWEEN DIET QUALITY IN CHILDHOOD AND ADULTHOOD AND KNEE SYMPTOMS IN YOUNG ADULTS. (2nd June 2020) - Meng, T.; Wilson, J.; Venn, A.; Cicuttini, F.; March, L.; Cross, M.; Dwyer, T.; Blizzard, L.; Jones, G.; Laslett, L.; Antony, B.; Ding, C.
Abstract : Background: Knee osteoarthritis (OA) is the most prevalent joint disease worldwide, but no disease-modifying treatments are available. Existing treatments largely focus on relieving symptoms, but they may have substantial adverse effects. Identifying risk factors affecting knee symptoms is important for developing safer prevention strategies of knee OA symptoms. Objectives: To describe the associations between diet quality in childhood and adulthood and knee symptoms in young adults. Methods: Participants were from the Australian Schools Health and Fitness Survey (ASHFS) in 1985, which was conducted to provide benchmark data on the health and fitness of Australian schoolchildren. During 2004-2006, participants were followed up in the Childhood Determinants of Adult Health (CDAH) Study. Dietary measures were collected in ASHFS (aged 10-15 years) and CDAH Study (aged 26-36 years) using food questionnaires. Diet quality was assessed by Dietary Guidelines Index (DGI), reflecting the adherence to Australian Dietary Guidelines. The DGI comprises 9 components and its maximum possible score is 100. A higher score indicated higher diet quality. During 2008-2010, participants (aged 31-41years) were followed up in the CDAH Knee Study. Knee symptoms were collected using Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Zero-inflated negative binomial regression analyses were used to assess the associations between diet quality and knee symptoms. Age, sex, body mass index, physical activity, total energy intake, and knee injury history were included as potential confounders based on biological plausibility. Results: A total of 399 participants (48.4% were female) were included in analysis. The average childhood and adult DGI was 46.5 and 55.4, respectively. The prevalence of knee pain, stiffness and dysfunction was 35.1%. 31.6% and 39.9%, respectively. The overall childhood DGI was not associated with adult knee symptoms. However, the limited intake of discretionary foods in childhood was associated with lower pain (Mean ratio (MR): 0.96, 95% confidence interval (CI): 0.92-1.00) and dysfunction (MR: 0.94, 95% CI: 0.90-0.99). The overall adult DGI was not associated with knee symptoms. However, replacing saturated fats with unsaturated fats in adulthood was associated with lower WOMAC (Pain: MR 0.93, 95% CI 0.87-0.99; stiffness: MR 0.93, 95% CI 0.87-0.99; dysfunction: MR 0.91, 95% CI 0.83-0.99), drinking water in adulthood was associated with lower stiffness (MR: 0.90, 95% CI: 0.83-0.99), and fruit intake in adulthood was associated with lower dysfunction (MR: 0.90, 95% CI: 0.81-0.99). Moreover, higher DGI score for dairy in adulthood was associated with higher WOMAC (Pain: MR 1.07, 95% CI 1.00-1.13; stiffness: MR 1.13, 95% CI 1.05-1.21; dysfunction: MR 1.11, 95% CI 1.02-1.21). The overall score change of DGI from childhood to adulthood was not associated with adult knee symptoms. However, the score change of replacing saturated fats with unsaturated fats from childhood to adulthood was associated with lower stiffness (MR 0.89, 95% CI 0.80-0.98), and the score change of fruit intake was associated with lower dysfunction (MR 0.92, 95% CI 0.86-0.99). Conclusion: Several DGI component scores in childhood and adulthood and some changes of DGI component score from childhood to adulthood were associated with knee symptoms in young adults. The results suggested that early-life diet quality may affect knee symptoms in young adults. Disclosure of Interests: None declared